Comparación del tratamiento de neumonía intrahospitalaria con tigeciclina y colistina en el Hospital Almanzor Aguinaga Asenjo EsSalud- Chiclayo, 2017 - Chávez Alcántara, Leyly Nataly (2019)
The aim of this report was to compare the treatment of in-hospital pneumonia with tigecycline and colistin. To do this, the search for information was made through Pubmed, where the published evidence was evaluated. The intrahospital pneumonia treatments presented by the Clinical Practice Guidelines were used: Edgardo Rebagliati Martins EsSalud-Lima National Hospital, Argentina, Mexico and the National Institute of Excellence in Health and Care (NICE), in comparison with the Almanzor Aguinaga Hospital Asenjo EsSalud - Chiclayo, 2017. These data were collected through the pharmacotherapeutic follow-up sheets in the Intensive Care Unit Service. A similarity was observed in clinical practice guidelines: treatment of intrahospital pneumonia with colistin. It was concluded that the Hospital Almanzor Aguinaga Asenjo EsSalud-Chiclayo, 2017, shows similarity with the Clinical Practice Guide of the Edgardo Rebagliati Martins EsSalud National Hospital and the Clinical Guide Argentina, with the treatment of colistin, except with tigecycline. Unlike the Mexican Clinical Guide and NICE, which does not mention it